A new function of offset response in the primate auditory cortex: marker of temporal integration - Peirun Song; Haoxuan Xu; Hangting Ye; Xinyu Du; Yuying Zhai; Xuehui Bao; Ishrat Mehmood; Hisashi Tanigawa; Wanqiu Niu; Zhiyi Tu; Pei Chen; Tingting Zhang; et al. (Communications Biology, 2024)
Abstract Offset responses are traditionally viewed as indicators of sound cessation. Here, we investigate offset responses to auditory click trains, examining how they are modulated by inter-click intervals (ICIs) and train duration. Using extracellular recordings and electrocorticography (ECoG) in non-human primates, alongside electroencephalography (EEG) in humans, we show that offset responses are significantly influenced by both ICI and train length, thereby establishing them as markers of temporal integration. We introduce the concept of the ‘Neuronal Integrative Window’ (NIW), defined as the temporal span during which neurons integrate stimuli to produce or modulate the temporal integration signal. Our data reveal that on the neuronal level, the auditory cortex (AC) exhibits a more expansive NIW than the medial geniculate body (MGB), integrating stimuli over longer durations and showing a preference for larger ICIs. Furthermore, our results indicate that offset responses could serve as potential biomarkers for neurological and psychiatric conditions, highlighted by their sensitivity to pharmacological modulation with ketamine. This study advances our understanding of auditory temporal processing and proposes a novel approach for assessing and monitoring brain health.